Letter (copy) : Employment and Maintenance of Basque Boys - Tewson, Vincent
1940-01-17 038-0049-001 Secretary' s. HVT/FC/EK/540. 17th January, 1940. Mr. H. Siebert, Basque Boys Training Committee, 30, Eccleston Street, London, S.W.1. Dear Mr. Siebert, EMPLOYMENT AND MAINTENANCE OF BASQUE BOYS. I am in receipt of your letter of the 15th instant regarding the meeting of representatives of the National Joint Committee, the Basque Children's Committee and the Basque Boys Training Committee, to be held on the 19th instant at 11.30 a.m. In these times it is very difficult to make a definite promise, but I shall do my utmost to attend the meeting in question. Yours sincerely, Assistant Secretary. 292/946/38/49(I)